Repetitive transcranial magnetic stimulation for management of post-stroke impairments: An overview of systematic reviews - Woo-Jin Kim; Charlotte Rosselin; Bhasker Amatya; Pouya Hafezi; Fary Khan (Medical Journals Sweden, 2020)
Objective: To evaluate evidence from published systematic reviews of clinical trials to determine the effectiveness of repetitive transcranial magnetic stimulation (rTMS) in stroke population. Methods: The Cochrane Library, MEDLINE, CINAHL, EMBASE, and PubMed were searched for systematic reviews up to 15 January 2019. Three authors independently screened the reviews and assessed the methodological quality, using Assessment of Multiple Systematic Reviews (AMSTAR) appraisal tool. Quality of evidence for outcomes evaluated within the reviews was appraised with Grade of Recommendation, Assessment, Development and Evaluation (GRADE) tool. Results: Twelve reviews (n = 9,117 participants) evaluated the effectiveness of rTMS on motor and non-motor (aphasia, depression, dysphagia and cognition) functions. The rTMS protocols applied and outcomes measured were diverse amongst the selected reviews. The findings suggest beneficial effect of rTMS with: "moderate quality" evidence for dysphagia and hemineglect, "low to moderate quality" evidence for motor function (upper limb function, daily activities), and "low quality" evidence for aphasia and post-stroke depression. Conclusion: Despite widespread use of rTMS, high-quality evidence for its routine use for the treatment of stroke survivors is lacking. Further studies are required to establish differential roles of various protocols and long-term effects of rTMS in the stroke population.